Epidermal filaggrin deficiency mediates increased systemic T‐helper 17 immune response1111. (1st October 2016) - Bonefeld, C.M.; Petersen, T.H.; Bandier, J.; Agerbeck, C.; Linneberg, A.; Ross‐Hansen, K.; Stender, S.; Szecsi, P.B.; Johansen, J.D.; Geisler, C.; Thyssen, J.P.
Summary: Background: Cellular T‐helper (Th)17 infiltrates dominate skin inflammation in filaggrin‐deficient flaky tail ( ft/ft ) mice, and Th17 cells are found in both the skin and blood of patients with acute atopic dermatitis. However, the potential role of loss‐of‐function mutations in the filaggrin gene ( FLG ) for increased peripheral Th17 cells is unclear. Objectives: To study whether mutations in FLG influence the frequency of peripheral Th17 cells. Methods: We studied blood samples from six adults with mutations in FLG and five controls without mutations for frequencies of cytokine‐producing CD4 + T cells. We evaluated ft/ft mice and wild‐type (WT) control mice for interleukin (IL)‐17‐producing CD4 + T cells in naive mice and following 2, 4‐dinitrofluorobenzene (DNFB) challenge. In addition, the T‐cell receptor (TCR) Vβ‐chain repertoire was analysed by flow cytometry. Results: Human studies showed increased frequency of peripheral Th17 cells in FLG mutation carriers when compared with WT individuals. Mouse studies showed increased frequency of peripheral Th17 cells in adult ft/ft mice but not in 2‐week‐old ft/ft mice. Moreover, altered TCR Vβ‐chain repertoire was found in ft/ft mice when compared with WT mice. An increased frequency of CD4 + Vβ10 + T cells producing IL‐17 was found in the spleen of adult ft/ft mice when compared with WT mice. Finally, DNFB challenge induced an increased number of Th17 cells in ft/ft mice compared with WT mice. Conclusions: Deficiency of filaggrin appeared to be a driver of increased peripheral levels of Th17 cells. This increase must be acquired as peripheral Th17 cells were found in adult ft/ft mice but not in 2‐week‐old ft/ft mice indicating involvement of exogenous factors.